Validation of a Newton’s Laws Learning Module Based on Educational Robotics Using a Guided Inquiry Model to Enhance Students’ Learning Interest - Nia Nofrita Sari; Wawan Kurniawan; M. Furqon (Universitas Muhammadiyah Enrekang, 2025)
This research was motivated by the low learning interest of students in physics, particularly in Newton’s Laws, which is caused by the hectic schedule of students from morning until evening, resulting in limited time and motivation to study. To address this issue, a Newton’s Laws learning module based on educational robotics was developed using the guided inquiry model as a learning approach that emphasizes exploratory activities and conceptual understanding through direct experience. The development model applied in this study was the ADDIE model, limited to the development stage. The research subjects consisted of physics teachers, material experts, and media experts. Data were collected through interviews and Focus Group Discussions (FGD) to obtain feedback and validation of the developed product. Data analysis was conducted using quantitative descriptive analysis for validation results and qualitative analysis for FGD results. The validation results showed that the average score from material experts was 88.8%, and the average score from media experts was 90.75%, both of which fall into the very valid category. Based on these results, the Newton’s Laws learning module based on educational robotics using the guided inquiry model was declared very valid and feasible for use in physics learning. This medium is expected to increase students’ learning interest through a more engaging and meaningful learning experience.